Bioinformatic Analysis of the Perilymph Proteome to Generate a Human Protein Atlas - van Dieken, Alina; Staecker, Hinrich; Schmitt, Heike; Harre, Jennifer; Pich, Andreas; Roßberg, Willi; Lenarz, Thomas; Durisin, Martin; Warnecke, Athanasia (Frontiers in Cell and Developmental Biology, 2022)
The high complexity of the cellular architecture of the human inner ear and the inaccessibility for tissue biopsy hampers cellular and molecular analysis of inner ear disease. Sampling and analysis of perilymph may present an opportunity for improved diagnostics and understanding of human inner ear pathology. Analysis of the perilymph proteome from patients undergoing cochlear implantation was carried out revealing a multitude of proteins and patterns of protein composition that may enable characterisation of patients into subgroups. Based on existing data and databases, single proteins that are not present in the blood circulation were related to cells within the cochlea to allow prediction of which cells contribute to the individual perilymph proteome of the patients. Based on the results, we propose a human atlas of the cochlea. Finally, druggable targets within the perilymph proteome were identified. Understanding and modulating the human perilymph proteome will enable novel avenues to improve diagnosis and treatment of inner ear diseases.